Hydrangea‐Like CuS with Irreversible Amorphization Transition for High‐Performance Sodium‐Ion Storage. Issue 11 (8th April 2020) - Yang, Zu‐Guang; Wu, Zhen‐Guo; Hua, Wei‐Bo; Xiao, Yao; Wang, Gong‐Ke; Liu, Yu‐Xia; Wu, Chun‐Jin; Li, Yong‐Chun; Zhong, Ben‐He; Xiang, Wei; Zhong, Yan‐Jun; Guo, Xiao‐Dong
Abstract: Metal sulfides have been intensively investigated for efficient sodium‐ion storage due to their high capacity. However, the mechanisms behind the reaction pathways and phase transformation are still unclear. Moreover, the effects of designed nanostructure on the electrochemical behaviors are rarely reported. Herein, a hydrangea‐like CuS microsphere is prepared via a facile synthetic method and displays significantly enhanced rate and cycle performance. Unlike the traditional intercalation and conversion reactions, an irreversible amorphization process is evidenced and elucidated with the help of in situ high‐resolution synchrotron radiation diffraction analyses, and transmission electron microscopy. The oriented (006) crystal plane growth of the primary CuS nanosheets provide more channels and adsorption sites for Na ions intercalation and the resultant low overpotential is beneficial for the amorphous Cu‐S cluster, which is consistent with the density functional theory calculation. This study can offer new insights into the correlation between the atomic‐scale phase transformation and macro‐scale nanostructure design and open a new principle for the electrode materials' design. Abstract : A hydrangea‐like CuS microsphere with high geometrical symmetry and oriented (006) crystal plane growth is successfully constructed through a facile synthetic route. The oriented (006) crystal plane growth of the primary CuS nanosheets provide more channels and adsorption sites for Na ions intercalation, and the resultant low overpotential is beneficial for the amorphous Cu‐S cluster.